Changes in biomarkers after therapeutic intervention in temporal arteries cultured in Matrigel: a new model for preclinical studies in giant-cell arteritis. Issue 3 (27th April 2013) - Corbera-Bellalta, Marc; García-Martínez, Ana; Lozano, Ester; Planas-Rigol, Ester; Tavera-Bahillo, Itziar; Alba, Marco A; Prieto-González, Sergio; Butjosa, Montserrat; Espígol-Frigolé, Georgina; Hernández-Rodríguez, José; Fernández, Pedro L; Roux-Lombard, Pascale; et al.
Abstract : Background: Search for therapeutic targets in giant-cell arteritis (GCA) is hampered by the scarcity of functional systems. We developed a new model consisting of temporal artery culture in tri-dimensional matrix and assessed changes in biomarkers induced by glucocorticoid treatment. Methods: Temporal artery sections from 28 patients with GCA and 22 controls were cultured in Matrigel for 5 days in the presence or the absence of dexamethasone. Tissue mRNA concentrations of pro-inflammatory mediators and vascular remodelling molecules was assessed by real-time RT-PCR. Soluble molecules were measured in the supernatant fluid by immunoassay. Results: Histopathological features were exquisitely preserved in cultured arteries. mRNA concentrations of pro-inflammatory cytokines (particularly IL-1β and IFNγ), chemokines (CCL3/MIP-1α, CCL4/MIP-1β, CCL5/RANTES) and MMP-9 as well as IL-1β and MMP-9 protein concentrations in the supernatants were significantly higher in cultured arteries from patients compared with control arteries. The culture system itself upregulated expression of cytokines and vascular remodelling factors in control arteries. This minimised differences between patients and controls but underlines the relevance of changes observed. Dexamethasone downregulated pro-inflammatory mediator (IL-1β, IL-6, TNFα, IFNγ, MMP-9, TIMP-1, CCL3 and CXCL8) mRNAs but did not modify expression of vascular remodelling factors (platelet derived growth factor, MMP-2 and collagens I and III). Conclusions: Differences in gene expression in temporal arteries from patients and controls are preserved during temporal artery culture in tri-dimensional matrix. Changes in biomarkers elicited by glucocorticoid treatment satisfactorily parallel results obtained in vivo. This may be a suitable model to explore pathogenetic pathways and to perform preclinical studies with new therapeutic agents.